The Underlying Process of Prosocial Behavior Among Soldiers: A Terror Management Theory Perspective - Heller, Ido; Halabi, Samer (Frontiers in Psychology, 2022)
The mortality salience (MS) hypothesis postulates that anxiety elicited by mortality awareness leads people to develop negative emotions toward those who hold values inconsistent with their worldview faith. We explored this hypothesis in a sample of 76 Israeli combat soldiers, who were asked to reflect on either their mortality or dental pain. Subsequently, participants reported their motivation to help a father in need who was either an Arab (outgroup) or a Jewish Israeli (ingroup), as well as their perceptions of threat by Arab Israelis. Regression analysis indicated that mortality reminders intensified soldiers’ perception of threat by the outgroup, leading to an increased desire to assist a Jewish-Israeli father, and a decreased motivation to help an Arab-Israeli one. The findings demonstrate the pronounced effects of MS on soldiers involved in frequent combat actions in terms of evoking negative emotions leading to reluctance to help unarmed civilian outgroup members. Recommendations for soldiers’ pre-deployment psychoeducation sessions are provided.